2019
DOI: 10.1108/jfep-09-2018-0140
|View full text |Cite
|
Sign up to set email alerts
|

Real interest rate, income and bank loans: panel evidence from Egypt

Abstract: Purpose This paper aims to examine the effectiveness of monetary policy on bank loans in Egypt using generalized method of moments (GMM) model. Also, it investigates the impact of bank level variables, namely, total assets, liquidity, capital and income on bank loans. It develops the equation of loans, which is introduced by Ehrmann et al. (2002) using bank level variables such as income and the interaction between income and interest rate. Design/methodology/approach This paper examines the impact of moneta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(119 reference statements)
1
2
0
Order By: Relevance
“…A lower domestic price induced by a negative monetary policy shock causes the real exchange rate to depreciate promoting the country's exports and decreasing its imports and thereby improving the trade balance followed by an appreciation of the real exchange rate. The findings are consistent with previous studies by (Amidu & Wolfe (2008: Shokr & Al-Gasaymeh, 2018: Shokr et al 2019: Shokr, 2020) who found out a significant relationship between monetary policy and banks' lending. However, the findings of the study are contrary to Ogunyomi (2011) who found out that monetary policy was ineffective for increasing the volume loans and advances.…”
Section: The Effects Of Foreign Monetary Policy On Domestic and Forei...supporting
confidence: 93%
See 1 more Smart Citation
“…A lower domestic price induced by a negative monetary policy shock causes the real exchange rate to depreciate promoting the country's exports and decreasing its imports and thereby improving the trade balance followed by an appreciation of the real exchange rate. The findings are consistent with previous studies by (Amidu & Wolfe (2008: Shokr & Al-Gasaymeh, 2018: Shokr et al 2019: Shokr, 2020) who found out a significant relationship between monetary policy and banks' lending. However, the findings of the study are contrary to Ogunyomi (2011) who found out that monetary policy was ineffective for increasing the volume loans and advances.…”
Section: The Effects Of Foreign Monetary Policy On Domestic and Forei...supporting
confidence: 93%
“…Civcir and Varoglu (2019) investigated the effect of monetary policy in the United States and the Euro area and found out that inflation, domestic industrial production interest rates real effective exchange rates respond to change in monetary policy. Shokr (2020) in his study on monetary policy effect confirms a significant impact of real interest rates on bank loan supply in Egypt, which highlights the essence of the bank lending channel in Egypt. Shokr and Karim (2021) examined the impact of international monetary policy shocks on bank loans and other macroeconomic indicators in Egypt and found out that foreign monetary policy shocks significantly affect loans, inflation, interest rates, and output in Egypt.…”
Section: Empirical Studies On Impact Of Monetary Policy On Banksmentioning
confidence: 78%
“…Nguyen et al (2018) showed that trade openness significantly and negatively impacts domestic credit after analysing 33 emerging countries (including three African countries) from 2002 to 2015, also using the system GMM. Shokr (2020) found that real interest rates had a significant and negative effect on bank loans in Egypt when the GMM technique was applied to panel data during the period of 1996-2014. Modugu and Dempere (2022) reported similar results: an increase in monetary policy rates reduced bank lending in 20 SSA countries from 2010 to 2019 using the system GMM.…”
Section: Moments Quantile Regression Analysismentioning
confidence: 99%